Bifurcation in a Class of Planar Piecewise Smooth Systems with 3-Parameters (Communications in Mathematical Research, 2021)
This paper is concerned with the bifurcation properties on the line ofdiscontinuity of planar piecewise smooth systems. The existence of equilibria andperiodic solutions with sliding motion in a class of planar piecewise smooth systemswith 3-parameters is investigated in this paper using the theory of differential inclusion and tools of Poincaré maps.
Keywords: piecewise smooth system; line of discontinuity; equilibria; periodic solution with sliding motion; bifurcation.